Analysis of the Spatial Thinking Ability of XI Social Students Through Map Media on the Material of Indonesia as the World's Maritime Axis at SMA Santo Mikhael Pangururan - Sirait, Elyasabeth; Ahyuni, Ahyuni (JPG (Jurnal Pendidikan Geografi), 2025)
The study analyzes students' spatial thinking abilities using map media on the topic of Indonesia as the World’s Maritime Axis in class XI IPS at SMA Santo Mikhael Pangururan. A comparative descriptive method with a quantitative quasi-experimental design was applied. The sample consisted of 36 students in both the control (XI Social 3) and experimental (XI Social 1) classes, selected through purposive sampling. Data were collected using a test based on Jo and Bednarz's four spatial thinking components, consisting of 10 essay questions. Validity and reliability tests confirmed that 10 questions were valid. Pretest results in the control class showed scores for Non-Spatial (24.11), Primitive Spatial (20.38), Simple Spatial (6.44), and Complex Spatial (0.27). Posttest results increased slightly except for Complex Spatial, which remained the same. The experimental class showed more significant improvement, with pretest scores of Non-Spatial (17.5), Primitive Spatial (13.75), Simple Spatial (7.97), and Complex Spatial (0.97). After the intervention, all components increased, but Complex Spatial remained low. The N Gain test results showed a moderate improvement in the experimental class (0.59) compared to a low improvement in the control class (0.15). Statistical tests confirmed a significant difference (Sig. 2-tailed = 0.000 < 0.05), indicating that map media effectively enhanced students' spatial thinking abilities. The four spatial thinking components—non-spatial, primitive spatial, simple spatial, and complex spatial—help students connect visual and symbolic information, recognize locations, understand spatial relationships, and analyze geographical changes. The findings highlight the benefits of map media in improving spatial thinking, particularly in learning about Indonesia as the World’s Maritime Axis.Keywords: Spatial Thinking Ability, Maps, Indonesia as the World's Maritime Axis